Creating a 'monster': the National Youth Service pre-university training programme, student activism and the Kenyan state, 1978–90. (16th January 2019) - Melchiorre, Luke
Abstract: In May 1984, the Kenyan government of Daniel arap Moi introduced a National Youth Service pre-university training programme (NYSPUT) for prospective university students. The programme was designed to instil discipline in Kenyan university students and inculcate them with a sense of loyalty and commitment to the Moi regime prior to their arrival on campus. This article argues that, in practice, however, the scheme had unintended consequences: it served to alienate student recruits from the ruling party and helped radicalize a small but vocal group of student activists, who, when they arrived on campus, confronted the Moi state with some of its most defiant political challenges of the 1980s. Relying on extensive interviews with former student recruits and archival research, this article highlights the key role that the NYSPUT played in shaping Kenya's young generation of 1980s student activists, who represented one of the most united and militant student movements in the country's history. Résumé: En mai 1984, le gouvernement kenyan de Daniel arap Moi mit en place un programme de formation pré-universitaire dans le cadre du Service national de la jeunesse (NYSPUT) destiné aux futurs étudiants universitaires. Ce programme visait à instiller la discipline aux étudiants universitaires kenyans et à leur inculquer le sens de la loyauté et de l'engagement envers le régime de Moi avant leur arrivée sur le campus universitaire. Or, dans la pratique, l'article suggère que le programme a eu un effet pervers : il a servi à aliéner les nouveaux étudiants du parti au pouvoir et aidé à radicaliser un groupe d'étudiants activistes faible en nombre mais fort en voix qui, lorsqu'ils sont arrivés sur le campus, ont compté parmi ceux qui ont le plus défié la politique du gouvernement Moi dans les années 1980. S'appuyant sur de longs entretiens avec d'anciens nouveaux étudiants et sur des recherches archivistiques, cet article souligne le rôle essentiel qu'a joué le programme NYSPUT dans le façonnage de la jeune génération d'étudiants activistes kenyans des années 1980, qui a représenté l'un des mouvements étudiants les plus unis et les plus militants de l'histoire du pays.